Pengembangan User Interface (UI) Dan User Experience (UX) Website KONI Kendal Dengan Metode Design Thinking - Anwar, Sariyun Naja; Soelistijadi, R.; Diartono, Dwi Agus; Cahyono, Taufiq Dwi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
KONI Kendal district has been informing about sports activities using offline media and online media in the form of Instagram. The more the agenda for sports activities increases, the more information is conveyed and this creates complexity in conveying information. For this reason, a website was developed that can combine document, photo and video formats and can be integrated with other social media platforms such as Facebook, Twitter and Telegram. Implementation of User Interface and User Experience in website development to meet user needs. This research designed a UI/UX prototype for the KONI district website. Kendal with the design thinking method. The design thinking method is a problem solving method that focuses on users with five stages that must be gone through, namely empathize, define, ideate, prototype and test. The results of this research are a prototype of the Kendal district KONI website, then tested using the usability scale (SUS) system. It is hoped that the results can improve communication by providing information related to sports to the community.